Experimental measurement of organizational citizenship behavior: Altruism, risk aversion and sportsmanship - Torres-Carballo, Federico (2018)
The measurement of individual characteristics is essential for the recruitment and skills assessment to only mention two key areas of human resource management. Experimental techniques can contribute to a closer measuring behaviors generated in work environments, behaviors that exceed expectations and lead to an outstanding performance of the organization. This paper addresses two components of Organizational Citizenship Behavior with experimental techniques: altruism and sportsmanship. This analysis adds risk aversion.